This lecture should be primarily a review for you of properties of spin one-half. I do suspect that some of the identities derived here, especially the exponential disentangling identity, will be new for you.
Recall the spin operators and eigenstates. The states \(|\uparrow ; z\rangle\) and \(|\downarrow ; z\rangle\) are eigenstates of \(\hat{S}_z\), which satisfy
\[\begin{aligned} & \left.\begin{array}{l} \hat{S}_{z}|\uparrow ; z\rangle=\frac{\hbar}{2}|q ; z\rangle \quad \\ \hat{S}_{z}|\downarrow ; z\rangle=-\frac{\hbar}{2}|\downarrow ; z\rangle \end{array}\right\} \text { eigenstates. } \end{aligned}\]
Next, we discuss the raising and lowering operators. Define \(\hat{S}_{+}\) and \(\hat{S}_{-}\) to connect these states \[\begin{aligned} & \hat{S}_+\mid \uparrow ; z)=0, \quad \hat{S}_+|\downarrow ; z\rangle=\hbar|\uparrow ; z\rangle \\ & \hat{S}_-|\uparrow ; z\rangle=\hbar|\downarrow ; z\rangle, \quad \hat{S}_-\mid \downarrow ; z\rangle=0. \end{aligned}\]
Compute their commutators by acting the operator each, in turn, onto the states. Note that the commutator is computed via the action on the states themselves, using the above rule. We cannot determine them any other way. We have
\[\begin{aligned} & \left(\hat{S}_+\hat{S}_- - \hat{S}_-\hat{S}_{+}\right)|\uparrow ; z\rangle=\hbar^{2}|\uparrow ; z\rangle=2 \hbar \hat{S}_{z}|\uparrow ; z\rangle \\ & \left(\hat{S}_+\hat{S}_--\hat{S}_-\hat{S}_{+}\right)|\downarrow ; z\rangle=-\hbar^{2}|\downarrow ; z\rangle=2 \hbar \hat{S}_{z}|\downarrow ; z\rangle \end{aligned}\]
So \(\boxed{\quad\left[\hat{S}_{+},
\hat{S}_{-}\right]=2 \hbar \hat{S}_{z}}\)
Similarly: \[\begin{aligned} & \left(\hat{S}_{z} \hat{S}_{+}-\hat{S}_{+} \hat{S}_{z}\right)|\uparrow ; z\rangle=0=\hat{S}_{+}|\uparrow ; z\rangle \\ & \left(\hat{S}_{z} \hat{S}_{+}-\hat{S}+\hat{S}_{z}\right)|\downarrow ; z\rangle=\hbar^{2}|\downarrow ; z\rangle=\hbar \hat{S}_{+}|\downarrow ; z\rangle \end{aligned}\]
So \(\boxed{\left[\hat{S}_{z},
\hat{S}_{+}\right]=\hbar \hat{S}_{+}}\). You can verify yourself
that \(\boxed{\left[\hat{S}_{z},
\hat{S}_{-}\right]=-\hbar \hat{S}_{-}}\).
Please ensure that you are comfortable calculating the commutators in
this way, by acting the operators onto the states in the order provided
and determining what the final result is. Because we acted them on all
the states in our Hilbert space, we can use this to determine the
commutation rule for the operators themselves. This is how we obtained
our summary equations.
These three commutation relations are the \(S U(2)\) algebra.
Next, we move on to determine the Cartesian spin operators. If we define \(\hat{S}_{x}=\frac{1}{2}\left(\hat{S}_{+}+\hat{S}_{-}\right)\) and \(\hat{S}_{y}=\frac{1}{2 i}\left(\hat{S}_{+}-\hat{S}_{-}\right)\), then \(\hat{S}_{+}=\hat{S}_{x}+i \hat{S}_{y}\) and \(\hat{S}_{-}=\hat{S}_{x}-i \hat{S}_{y}\). The algebra of the Cartesian spins follows:
\[\begin{aligned} {\left[\hat{S}_{x}, \hat{S}_{y}\right] } & =\frac{1}{4 i}\left[\hat{S}_{+}+\hat{S}_{-}, \hat{S}_{+}-\hat{S}_{-}\right] \\ & =\frac{1}{4 i}\left\{\left[\hat{S}_{+}, \hat{S}_{+}\right]-\left[\hat{S}_{+}, \hat{S}_{-}\right]+\left[\hat{S}_{-}, \hat{S}_{+}\right]-\left[\hat{S}_{x}, \hat{S}\right]\right\} \\ & =\frac{1}{4 i}\left[-2 \hbar \hat{S}_{z}-2 \hbar \hat{S}_{z}\right]=i \hbar \hat{S}_{z} \end{aligned}\] where we used the commutation relations that we already knew to evaluate them.
You can verify (and should) that we have \[\left[\hat{S}_{i}, \hat{S}_{j}\right]=i \hbar \sum_{k} \varepsilon_{i j k} \hat{S}_{k}\] which is the standard form for angular momentum commutators. Here, \(\varepsilon_{\text {ijk }}\) is the completely antisymmetric tensor, which satisfies \(\varepsilon_{123}=\varepsilon_{231}=\varepsilon_{312}=1\) and \(\varepsilon_{132}=\varepsilon_{321}=\varepsilon_{213}=-1\), and all others vanish. Note we freely use 1, 2, 3 or \(x\), \(y\), \(z\). It should be clear from the context what we mean.
From this relation, we can compute the commutation relation of the total spin squared with the Cartesian angular momentum operators. We have \[\left[\hat{S}^{2}, \hat{S}_{j}\right]=0.\]
Proof: \(\quad \hat{S}^{2}=\sum_{i} \hat{S}_{i} \hat{S}_{i}\) so \[\begin{aligned} {\left[\hat{S}^{2}, \hat{S}_{j}\right] } & =\sum_{i}\left[\hat{S}_{i} \hat{S}_{i}, \hat{S}_{j}\right]=\sum_{i}\left(\hat{S}_{i}\left[\hat{S}_{i}, \hat{S}_{j}\right]+\left[\hat{S}_{i}, \hat{S}_{j}\right] \hat{S}_{i}\right) \\ & =i \hbar \sum_{i} \sum_{k}\left(\hat{S}_{i} \varepsilon_{i j k} \hat{S}_{k}+\varepsilon_{i j k} \hat{S}_{k} \hat{S}_{i}\right) \\ & =i \hbar \sum_{i k} \varepsilon_{i j k}\left(\hat{S}_{i} \hat{S}_{k}+\hat{S}_{k} \hat{S}_{i}\right). \end{aligned}\] The claim is that this is zero. To see this let \(i \rightarrow k^{\prime}\) and \(k \rightarrow i^{\prime}\) \[\begin{aligned} & =i \hbar \sum_{i^{\prime} k^{\prime}} \varepsilon_{k^{\prime} j i^{\prime}}\left(\hat{S}_{k^{\prime}} \hat{S}_{i^{\prime}}+\hat{S}_{i^{\prime}} \hat{S}_{k^{\prime}}\right) \\ & =i \hbar \sum_{i^{\prime} k^{\prime}}\left(-\varepsilon_{i^{\prime} j k^{\prime}}\right)\left(\hat{S}_{i^{\prime}} \hat{S}_{k^{\prime}}+\hat{S}_{k^{\prime}} \hat{S}_{i^{\prime}}\right) \end{aligned}\] Since \(\varepsilon_{i j k}=-\varepsilon_{k j i}\). Now drop the primes \[=-i \hbar \sum_{i k} \varepsilon_{i j k}\left(\hat{S}_{i} \hat{S}_{k}+\hat{S}_{k} \hat{S}_{i}\right)\] Anything equal to its negative must vanish, so \(\left[\hat{S}^{2}, \hat{S}_{j}\right]=0\).
Let’s compute \(\hat{S}^{2}|\sigma ;
z\rangle\) with \(\sigma=\uparrow
\text{or} \downarrow\). First, we express the square of the spin
in the spherical basis, because we know what those operators do when
acting on states: \[\begin{aligned}
\hat{S}^{2}=\hat{S}_{x}^{2}+\hat{S}_{y}^{2}+\hat{S}_{z}^{2} &
=\frac{1}{4}\left(\hat{S}_{+}+\hat{S}_{-}\right)^{2}-\frac{1}{4}\left(\hat{S}_{z}-\hat{S}_{-}\right)^{2}+\hat{S}_{z}^{2}
\\
& =\frac{1}{2}\left(\hat{S}_+\hat{S}_{-}+\hat{S}_{-}
\hat{S}_{+}\right)+\hat{S}_{z}^{2}
\end{aligned}\] Then we evaluate directly on states. So, acting
on the up spin gives \[\begin{aligned}
\hat{S}^{2}|\uparrow ; z \rangle =\frac{1}{2}\left(\hat{S}_{+}
\hat{S}_{-}+\hat{S}_- \hat{S}_{+}\right)| \uparrow ;
z\rangle+\hat{S}_{z}^{2}|\uparrow ; z\rangle \\
=\left(\frac{1}{2} \hbar^{2}+\frac{1}{4} \hbar^{2}\right)|\uparrow ;
z\rangle=\frac{3}{4} \hbar^{2}|\uparrow ; z\rangle
\end{aligned}\] And acting on the down spin gives \[\begin{aligned}
\hat{S}^{2}(\downarrow ; z) & =\frac{1}{2}\left(\hat{S}_{+}
\hat{S}_{-}+\hat{S}_{-} \hat{S}_{+}\right) \rvert\, \downarrow ;
z\rangle+\hat{S}_{z}^{2}|\downarrow ; z\rangle \\
& =\frac{3}{4} \hbar^{2}(\downarrow ; z)
\end{aligned}\]
as well. Hence, \(|\sigma ; z\rangle\)
is an eigenstate of both \(\hat{S}^{2}\) and \(\hat{S}_{z}\) !
We next look at the matrix representations of spin. Assume we have an arbitrary superposition of states \[|\psi\rangle=\alpha|\uparrow ; z\rangle+\beta|\downarrow ; z\rangle.\] We let the column vector \(\binom{\alpha}{\beta}\) denote the state \(|\psi\rangle\). The operators \(\hat{S}_{i}\) are represented by two-dimensional matrices in this space. For example \[\begin{array}{rl} \hat{S}_{z} \mid \hat{\uparrow} ; z\rangle=\frac{\hbar}{2}|\uparrow ; z\rangle \\ \hat{S}_{z} \mid \downarrow ; z \rangle=\frac{\hbar}{2}|\downarrow ; z\rangle \end{array} \Leftrightarrow \frac{\hbar}{2}\left(\begin{array}{cc} 1 & 0 \\ 0 & -1 \end{array}\right)\binom{1}{0}=\frac{\hbar}{2}\binom{1}{0} \\ \text{ and } \frac{\hbar}{2}\left(\begin{array}{cc} 1 & 0 \\ 0 & -1 \end{array}\right)\binom{0}{1}=-\frac{\hbar}{2}\binom{0}{1}.\] The matrix representing the operator is \[M_{\sigma \sigma^\prime}=\left\langle\sigma ;z\right| \hat{S}_{i}\left|\sigma^{\prime} ; z\right\rangle\] which includes 4 numbers for the matrix from the different choices of \(\sigma\) and \(\sigma'\).
Let’s compute the matrix for \(\hat{S}_{y}\)
\[\begin{aligned}
& S_{\sigma \sigma^{\prime}}^{y}=\langle\sigma ; z|
\hat{S}_{y}\left|\sigma^{\prime} ; z\right\rangle=\frac{1}{2
i}\langle\sigma ; z| \hat{S}_{+}-\hat{S}_{-}\left|\sigma^{\prime} ;
z\right\rangle \\
& \sigma^{\prime}=\uparrow:\left(\hat{S}_{+}-\hat{S}_{-}\right) \mid
\uparrow ; z\rangle=-\hbar \mid \downarrow ; z\rangle \Rightarrow
S_{\uparrow \uparrow}^{y}=0,~ \text{ } S_{
\downarrow \uparrow}^{y}=\frac{i \hbar}{2} \\
& \sigma^{\prime}=\downarrow:\left(\hat{S}_{+}-\hat{S}_{-}\right)
\mid \downarrow ; z\rangle=\hbar|\uparrow ; z\rangle \Rightarrow
S_{\uparrow \downarrow}^{y}=-\frac{i \hbar}{2},~ \text{}
\hat{S}_{\downarrow \downarrow}^{y}=0.
\end{aligned}\] So \(\hat{S}_{y}=\frac{\hbar}{2}\left(\begin{array}{cc}0
& -i \\ i & 0\end{array}\right)\). Similarly, we have
\(\hat{S}_{x}=\frac{\hbar}{2}\left(\begin{array}{ll}0
& 1 \\ 1 & 0\end{array}\right) \quad \text{and}
\quad\hat{S}_{z}=\frac{\hbar}{2}\left(\begin{array}{cc}1 & 0 \\ 0
& -1\end{array}\right)\).
We call \(\sigma_{i}\) the Pauli
matrices \[\sigma_{x}=\left(\begin{array}{ll}
0 & 1 \\
1 & 0
\end{array}\right) \quad \sigma_{y}=\left(\begin{array}{cc}
0 & -i \\
i & 0
\end{array}\right) \quad \sigma_{z}=\left(\begin{array}{cc}
1 & 0 \\
0 & -1
\end{array}\right).\] Note that \(\sigma_{i}^{2}=\left(\begin{array}{ll}1 & 0 \\
0 & 1\end{array}\right) \Rightarrow S_{\sigma
\sigma^\prime}^2=\frac{\hbar^{2}}{4} \times 3
\times\left(\begin{array}{cc}1 & 0 \\ 0 &
1\end{array}\right)\)
These matrices also anticommute. To see this go back to our spin
commutators \[\hat{S}_{x}
\hat{S}_{y}-\hat{S}_{y} \hat{S}_{x}=i \hbar \hat{S}_{z}.\]
Multiply on left by \(\hat{S}_{x}\) and
on right by \(\hat{S}_{x}\) \[\begin{array}{r}
\hat{S}_{x}^{2} \hat{S}_{y}-\hat{S}_{x} \hat{S}_{y} \hat{S}_{x}=i \hbar
\hat{S}_{x} \hat{S}_{z} \\
\hat{S}_{x} \hat{S}_{y} \hat{S}_{x}-\hat{S}_{y} \hat{S}_{x}^{2}=i \hbar
\hat{S}_{z} \hat{S}_{x}.
\end{array}\] Now substitute in the Pauli matrices \[\begin{aligned}
& \frac{\hbar^{3}}{8}\left[\sigma_{x}^{2} \sigma_{y}-\sigma_{x}
\sigma_{y} \sigma_{x}\right]=i \frac{\hbar^{3}}{4} \sigma_{x} \sigma_{z}
\\
& \frac{\hbar^{3}}{8}\left[\sigma_{x} \sigma_{y}
\sigma_{x}-\sigma_{y} \sigma_{x}^{2}\right]=i \frac{i \hbar^{3}}{4}
\sigma_{z} \sigma_{x}.
\end{aligned}\] Add (and recall \(\sigma_{x}^{2}=\mathbb{1}\) ): \[\begin{gathered}
\frac{\hbar^{3}}{8}\left[\sigma_{y}-\sigma_{y}\right]=i
\frac{\hbar^{3}}{4}\left(\sigma_{x} \sigma_{z}+\sigma_{z}
\sigma_{x}\right) \\
0=\sigma_{x} \sigma_{z}+\sigma_{z} \sigma_{x}
\end{gathered}\] and it is obvious this holds for other
permutations too.
Hence, we have derived that \[\begin{aligned}
\sigma_{i} \sigma_{j} & =\frac{1}{2}\left[\sigma_{i}
\sigma_{j}+\sigma_{j} \sigma_{i}+\sigma_{i} \sigma_{j}-\sigma_{j}
\sigma_{i}\right] \\
& =\frac{1}{2} \delta_{i j} \times 2 \mathbb{1}+\frac{1}{2} i 2
\varepsilon_{i j k} \sigma_{k} \\
\text{ or } \sigma_{i} \sigma_{j} & =\delta_{i j} \mathbb{1}+i
\varepsilon_{i j k} \sigma_{k}
\end{aligned}\] This last equation is an important relation to
remember about the product of two Pauli spin matrices.
Another interesting identity is the product of all 3 \[\begin{gathered}
\sigma_{x} \sigma_{y} \sigma_{z}=i \varepsilon_{123} \sigma_{z}
\sigma_{z}=i \mathbb{1} \\
\sigma_{x} \sigma_{y} \sigma_{z}=i \mathbb{1}.
\end{gathered}\]
Any \(2 \times 2\) matrix can be
expressed in terms of the identity and the 3 Pauli matrices. This is
called completeness over the space of \(2\times 2\) matrices.
Check: \(\quad \alpha \mathbb{1}+\beta
\sigma_{x}+\gamma \sigma_{y}+\delta
\sigma_{z}=\left(\begin{array}{cc}\alpha+\delta & \beta-i \gamma \\
\beta+i \gamma & \alpha-\delta\end{array}\right)\)
So to find \(\left(\begin{array}{ll}a & b
\\ c & a\end{array}\right)\), we set \(a=\alpha+\delta \quad b=\beta-i\gamma\)
\(c=\beta+i \gamma d=\alpha
\delta\)
or \(\alpha=\frac{a+d}{2} \quad
\beta=\frac{b+c}{2} \quad \gamma=\frac{i}{2}(b-c) \quad \text{and}\quad
\delta=\frac{a-d}{2}\).
We often write this as \(M=\alpha \mathbb{1}
+\mathbf{v} \cdot \mathbf{\sigma} \quad \mathbf{v}=\left(\frac{b+c}{2},
\frac{i}{2}(b-c), \frac{a-d}{2}\right)\).
Let’s get some practice working with these objects \[\begin{aligned}
(\mathbf{A} \cdot \mathbf{\sigma})(\mathbf{B} \cdot \mathbf{\sigma})
& =\sum_{i j} A_{i} B_{j} \sigma_{i} \sigma_{j} \\
& =\sum_{i j} A_{i} B_{j}\left(\delta_{i j} \mathbb{1}+i
\varepsilon_{i j k} \sigma_{k}\right) \\
& =\mathbf{A} \cdot \mathbf{B} \mathbb{1}+i \varepsilon_{i j k}
A_{i} B_{j} \sigma_{k} \\
& =\mathbf{A} \cdot \mathbf{B} \mathbb{1}+i(\mathbf{A} \times
\mathbf{B}) \cdot \mathbf{\sigma}
\end{aligned}\]
Note that if \(\mathbf{A}\) is parallel
to \(\mathbf{B}\), then \((\mathbf{A} \cdot \mathbf{\sigma})(\mathbf{B}
\cdot \mathbf{\sigma})=\mathbf{A} \cdot \mathbf{B} \mathbb{1}\).
This identity is a useful one to remember.
Next, we evaluate the matrix exponential: \[\operatorname{exp}[i \mathbf{v} \cdot
\mathbf{\sigma}]=\sum_{n=0}^{\infty} \frac{(i)^{n}}{n!}(\mathbf{v} \cdot
\mathbf{\sigma})^{n}.\] First separate out into even and odd
powers \[e^{i \mathbf{v} \cdot
\mathbf{\sigma}}=\sum_{n=0}^{\infty} \frac{(-1)^{n}}{(2 n)!}(\mathbf{v}
\cdot \mathbf{\sigma})^{2 n}+i \sum_{n=0}^{\infty} \frac{(-1)^{n}}{(2
n+1)!}(\mathbf{v} \cdot \mathbf{\sigma})^{2 n+1}.\]
But recall \((\mathbf{v} \cdot
\mathbf{\sigma})(\mathbf{v} \cdot \mathbf{\sigma})=v^{2}
\mathbb{1}\) so \[\begin{aligned}
& e^{i \mathbf{v} \cdot \mathbf{\sigma}}=\sum_{n=0}^{\infty}
\frac{(-1)^{n}}{(2 n)!}\left(v^{2}\right)^{n} \mathbb{1}+i \mathbf{v}
\cdot \mathbf{\sigma} \sum_{n=0}^{\infty} \frac{(-1)^{n}}{(2
n+1)!}\left(v^{2}\right)^{n} \\
& \boxed{e^{i \mathbf{v} \cdot \mathbf{\sigma}}=\cos |v|
\mathbb{1}+i \frac{\mathbf{v} \cdot \mathbf{\sigma}}{|v|} \sin |v|}
\end{aligned}\]
This is called the generalized Euler identity.
Let’s compute the similarity transformation of a Pauli matrix (corresponding to a rotation) \[e^{i \mathbf{v} \cdot \mathbf{\sigma}} \sigma_{j} e^{-i \mathbf{v} \cdot \sigma}.\] In general, such terms can involve an infinite series, as we will show in a later lecture via the Hadamard lemma, but in this case, we can explicitly calculate it. Just use our generalized Euler identity for each exponential, followed by our product rule for pairs of Pauli matrices: \[\begin{aligned} & e^{i \bar{v} \cdot \mathbf{\sigma}} \sigma_{j} e^{-i \mathbf{v} \cdot \mathbf{\sigma}}=\left(\cos |v| \mathbb{1}+i \frac{\mathbf{v} \cdot \mathbf{\sigma}}{|v|} \sin |v|\right) \sigma_{j}\left(\cos |\sigma| \mathbb{1}-i \frac{\mathbf{v} \cdot \mathbf{\sigma}}{|v|} \sin (v)\right) \\ & =\cos ^{2}|v| \sigma_{j}-i \frac{\cos |v| \sin |v|}{|v|}\left(\sigma_{j} \mathbf{v} \cdot \mathbf{\sigma}-\mathbf{v} \cdot \mathbf{\sigma} \sigma_{j}\right) +\frac{\sin ^{2}|v|}{|v|^{2}} \mathbf{v} \cdot \mathbf{\sigma} \sigma_{j} \mathbf{v} \cdot \mathbf{\sigma} \\ & =\cos ^{2}|v| \sigma_{j}-i \frac{\cos |v| \sin |v|}{|v|} \sum_{i}\left[\sigma_{j}, \sigma_{i}\right] v_{i}+\frac{\sin ^{2}|v|}{|v|^2} \sum_{i k} v_{i} v_{k} \sigma_{i} \sigma_{j} \sigma_{k} \\ & =\cos ^{2}|v| \sigma_{j}+\frac{\cos |v| \sin |v|}{v} \sum_{i k} 2 \varepsilon_{j i k} v_{i} \sigma_{k}+\frac{\sin ^{2}|v|}{|\sigma|^{2}} \sum_{i k} v_{i} v_{k} \sigma_{i} \sigma_{j} \sigma_{k} \end{aligned}\]
But \(\sum_{i k} v_{i} v_{k} \sigma_{i}
\sigma_{j} \sigma_{k}=\sum_{i k} v_{i} v_{k}\left[\delta_{i j}
\mathbb{1}+i \varepsilon_{i j l} \sigma_{l}\right] \sigma_{k}\).
So, we have that \[\begin{aligned}
\sum_{i k} v_{i} v_{k} \sigma_{i} \sigma_{j} \sigma_{k}&=v_{j}
\mathbf{v} \cdot \mathbf{\sigma}+i \sum_{i k l} v_{i} v_{k}
\varepsilon_{i j l}\left(\cancelto{0}{\delta_{l k}}+i \varepsilon_{l k
m} \sigma_m\right) \\
&=v_{j} \mathbf{v} \cdot \mathbf{\sigma}-\sum_{i k l m} v_{i} v_{k}
\varepsilon_{i j l} \varepsilon_{l k m} \sigma_{m} \\
&=v_{j} \mathbf{v} \cdot \mathbf{\sigma}-\sum_{i k m} v_{i}
v_{k}\left(\delta_{i k} \delta_{j m}-\delta_{i m} \delta_{j k}\right)
\sigma_{m} \\
&=v_{j} \mathbf{v} \cdot \mathbf{\sigma}-v^{2} \sigma_{j}+\mathbf{v}
\cdot \mathbf{\sigma} v_{j} \\
\text{So that}~~~~~&\\
e^{i \bar{v} \cdot \mathbf{\sigma}} \sigma_{j} e^{-i \mathbf{v} \cdot
\mathbf{\sigma}}&=\cos ^{2}|v| \delta_{j}+2 \frac{\cos |v| \sin
|v|}{|v|}(\mathbf{v} \times \mathbf{\sigma})_{j}+\frac{\sin
^{2}(v)}{|v|^{2}}\left(2 \mathbf{v} \cdot \mathbf{\sigma} v_{j}-v^{2}
\sigma_{j}\right).
\end{aligned}\]
Our last topic is on exponential disentangling. This is an identity most have not seen before. It is derived by factorizing the exponential of a combination of Pauli matrices into a product of three special Pauli matrices. First note that \(\sigma_{+}=\sigma_{x}+i \sigma_{y}=\left(\begin{array}{ll}0 & 2 \\ 0 & 0\end{array}\right)\) so
\[\begin{aligned}
\exp \left(\alpha \sigma_{+}\right) & =1+\alpha
\sigma_{+}+\frac{1}{2}
\alpha^{2}\left(\cancelto{0}{\sigma_{+}^2}\right)+\cdots \\
& =\left(\begin{array}{cc}
1 & 2 \alpha \\
0 & 1
\end{array}\right) \\
\exp \left(\alpha \sigma_{-}\right) & =\left(\begin{array}{cc}
1 & 0 \\
2 \alpha & 1
\end{array}\right)
\end{aligned}\]
That is, the exponential of raising or lowering Paulis is given by a sum
of just two terms. Now, let’s consider the following exponential \[\exp (\mathbf{v} \cdot
\mathbf{\sigma})=\left(\begin{array}{ll}
\cos |\sigma|+i \frac{v_{z}}{|\sigma|} \sin |v| & \left(i
\frac{v_{x}}{|{v}|}+\frac{v_{y}}{|v|}\right) \sin |v| \\
(\frac{i v_{x}}{|v|} - \frac{v_{y}}{|v|}) \sin|v| & \cos |v|-i
\frac{v_{z}}{|v|} \sin |v|
\end{array}\right)\]
We want to re-write it as \(\exp [
\alpha \sigma_{+}]
\exp \left[\beta \sigma_{z}\right] \exp \left[\gamma
\sigma_{-}\right]\), so we have \[\begin{aligned}
& \left(\begin{array}{cc}
1 & 2 \alpha \\
0 & 1
\end{array}\right)\left(\begin{array}{cc}
e^{\beta} & 0 \\
0 & e^{-\beta}
\end{array}\right)\left(\begin{array}{cc}
1 & 0 \\
2 \gamma & 1
\end{array}\right) \\
= & \left(\begin{array}{cc}
e^{\beta} & 2 \alpha e^{-\beta} \\
0 & e^{-\beta}
\end{array}\right)\left(\begin{array}{cc}
1 & 0 \\
2 \gamma & 1
\end{array}\right)=\left(\begin{array}{cc}
e^{\beta}+4 \alpha \gamma e^{-\beta} & 2 \alpha e^{-\beta} \\
2 \gamma e^{-\beta} & e^{-\beta}
\end{array}\right).
\end{aligned}\]
Comparing to the exponential, we have \[\begin{aligned}
& \cos |v|+i \frac{v_{z}}{|v|} \sin |v|=e^{\beta}+4 \alpha \gamma
e^{-\beta} \\
& \left(i \frac{v_{x}}{|\sigma|}+\frac{v_{y}}{|v|}\right) \sin |v|=2
\alpha e^{-\beta} \\
& \left(i \frac{v_{x}}{|v|}-\frac{v_{y}}{|v|}\right) \sin |v|=2
\gamma e^{-\beta} \\
& \cos |v|-i \frac{v_{z}}{|v|} \sin |v|=e^{-\beta},
\end{aligned}\]
First note that \(e^{\beta}\left(1+4 \alpha
\gamma e^{-2 \beta}\right)=\frac{1}{\cos|v|- i\frac{v_{z} }{|v|} \sin
|v|}\left(1+\sin ^{2}|v| (-\frac{v_{z}^{2}-v_{y}^{2}}{|
v|^{2}}\right))\)
\[\begin{aligned}
& =\frac{\cos |v|+i \frac{v_{z}}{|v|} \sin |v|}{\cos
^{2}|v|+\frac{v_{z}^{2}}{|v|^{2} }\sin ^{2} |v|}\left(1+\sin
^{2}|v|\left(\frac{v_{z}^{2}}{|v|^{2}}-1\right)\right) \\
& =\cos |v|+i \frac{v_{z}}{|v|} \sin |v|
\end{aligned}\]
So if we solve the bottom three equations, the top automatically
holds! This then gives us
\[\begin{aligned}
&\boxed{
\beta=-\ln \left[\cos |v|-i \frac{v_{z}}{|v|} \sin |v|\right] }\\
&\boxed{\alpha=\frac{1}{2}\left(\frac{i
v_{x}}{|v|}+\frac{v_{y}}{|v|}\right) \frac{\sin |v|}{\cos |v|-\frac{i
v_{z}}{|v|} \sin |v|} }\\
&\boxed{\gamma=\frac{1}{2}\left(\frac{i
v_{x}}{|v|}-\frac{v_{y}}{|v|}\right) \frac{\sin |v|}{\cos |v|-i
\frac{v_{z}}{|v|} \sin |v|}
}
\end{aligned}\] This identity is called the exponential
disentangling identity and it is an important one.
An important special case is when \(\boxed{v_{x}=v_{z}=0}\), then \[\boxed{ \beta=\ln \sec v_{y} \quad \alpha=\frac{1}{2} \tan v_{y} \quad \gamma=-\frac{1}{2} \tan v_{y} }\] This is your first taste of exponential disentangling. We will see more of it soon.
What is amazing about exponential disentangling is that is holds for any angular momentum, not just spin one half. But, we will have more to say about that later.